Clinical characteristics and serotype association of dengue and dengue like illness in Pakistan. - Najeeha Talat Iqbal; Kumail Ahmed; Aqsa Khalid; Kehkashan Imtiaz; Qamreen Mumtaz Ali; Tania Munir; Syed Faisal Mahmood; Unab Khan; Badar Afzal; Farah Naz Qamar; Jesse J Waggoner; Hannah Fenelon; et al. (PLoS Neglected Tropical Diseases)
Background Pakistan has been an endemic country for dengue virus since 1994, with a significant increase in cases reported in 2022 largely due to heavy rainfall and flooding. All four serotypes of the dengue virus (DENV) are present in Pakistan, with DENV 1 and DENV 2 being the most prevalent. The current study aims to explore the clinical presentations and features of dengue fever in a tertiary care hospital. Methodology We enrolled and studied 349 cases of suspected and confirmed dengue presenting for care at the Aga Khan University Hospital in Karachi between June 2021 and November 2023. Collected data on cases included clinical symptoms and laboratory results including qRT-PCR and serotype characterization. Findings The majority of subjects enrolled (75%) had mild disease without warning signs, while 11% exhibited warning signs, 1.4% had severe dengue, and 12.6% had no dengue diagnosis. Patients with severe dengue (SD) had significantly higher levels of liver enzymes (AST and ALT) compared to those with non-severe dengue (NSD) (AST; p = 0.024 and ALT; p = 0.047). Additionally, a higher grade of thrombocytopenia was significantly associated with hospitalization (p = 0.0008), and prolonged illness (p = 0.03). Both Platelet (p < 0.0001) and WBC counts (p = 0.001) were significantly lower in dengue PCR-positive patients in comparison to Dengue PCR-negative. Among those tested for dengue serotypes, DENV 1 (34%) and DENV 2 (45%) emerged as the predominant serotypes, with mixed infections accounting for 17%. The sensitivity of q-RT PCR was found to be 87.25% and the specificity of 68.35%. qRT-PCR detected 43.5% of cases with viral fever initially screened negative by IgM or NS1. Conclusion The epidemiology of dengue fever during a widespread outbreak in 2022 showed a predominance of DENV 1 and DENV 2 serotypes with milder phenotype of viral illness. Screening with rapid tests requires further confirmation by molecular assay in cases with dengue and dengue-like illness. The sensitivity of q-RT PCR using gold standard.